Wonder [videorecording (DVD)] - Chbosky, Stephen; Tremblay, Jacob; Roberts, Julia, 1967-; Wilson, Owen, 1968-; Patinkin, Mandy; Palacio, R. J. (Lions Gate Entertainment, 2018)
Based on the New York Times best-seller, this tells the incredibly inspiring and heartwarming story of August Pullman, a boy with facial differences who enters fifth grade, attending a mainstream elementary school for the first time.